2015
DOI: 10.1016/j.jnucmat.2015.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat treatment on U–Mo fuel foils with a zirconium diffusion barrier

Abstract: A monolith fuel design based on U-Mo alloy has been selected as the fuel type for conversion of the United States' high performance research reactors (HPRRs) from highly enriched uranium (HEU) to low-enriched uranium (LEU). In this fuel design, a thin layer of zirconium is used to eliminate the direct interaction between the U-Mo fuel meat and the aluminum-alloy cladding during irradiation. The co-rolling process used to bond the Zr barrier layer to the U-Mo foil during fabrication alters the microstructure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, excessive growth of the U10Mo/Zr interaction layer was observed with post-rolling heat treatment. Homogenization heat treatment at 1000°C prior to rolling also led to reduced variation in Mo content throughout the fuel, but was not reported to have any effect on grain size and morphology after rolling [15].…”
Section: γ-U10momentioning
confidence: 96%
See 2 more Smart Citations
“…However, excessive growth of the U10Mo/Zr interaction layer was observed with post-rolling heat treatment. Homogenization heat treatment at 1000°C prior to rolling also led to reduced variation in Mo content throughout the fuel, but was not reported to have any effect on grain size and morphology after rolling [15].…”
Section: γ-U10momentioning
confidence: 96%
“…The effects of post-rolling heat treatments were analyzed by Jue et al [15], and it was found that the homogeneity of the U10Mo fuel increased with respect to composition as annealing temperature increased, i.e. the extent of chemical banding decreased.…”
Section: γ-U10momentioning
confidence: 99%
See 1 more Smart Citation
“…The monolithic fuel plate microstructure that will be present in a fuel plate going into a reactor is intimately related to the fabrication processes employed to make it. 5,6 The characteristics of this microstructure must be well understood, since the ultimate fuel plate performance during irradiation will depend on the performance of the phases that compose this microstructure. Microstructural fea-tures are correlated to areas of interest within an as-fabricated fuel plate; the U-10Mo fuel foil, the Zr diffusion barrier, and the Al-6061 cladding are of interest, along with features at the U-10Mo/Zr, Zr/Al-6061 cladding, U-10Mo/ Al-6061 cladding, and Al-6061 cladding/Al-6061 cladding interfaces.…”
Section: Introductionmentioning
confidence: 99%